Spotlight on faculty member: Professor Mashitah Moho Yusoff, physical organic chemist - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Khairu Aidilnishah, Rizan Jalil; Mohd Asyrak, Deraman; Rajan, Jose; Aziah, Mohd Yusoff (Penerbit UMP, 2009)
Mashitah Mohd. Yusoff was born in Bukit Merta jam (Pulau Pinang) in 1962, an only child of retired civil servants. After completing early education at the Convent School and then the Science School in Bukit Mertajam, she left for the United States to study chemistry.